2015
DOI: 10.1016/j.jsams.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

High intensity interval exercise is an effective alternative to moderate intensity exercise for improving glucose tolerance and insulin sensitivity in adolescent boys

Abstract: A single bout of time efficient HIIE is an effective alternative to MIE for improving glucose tolerance and IS in adolescent boys immediately after exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
6
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(113 citation statements)
references
References 28 publications
(30 reference statements)
9
94
6
4
Order By: Relevance
“…Acute studies have proposed that HIIE increases glucose tolerance and insulin sensitivity (Cockcroft et al, 2015). This response to HIIE is due to a closed integration between the different body systems, especially the metabolic and immune systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute studies have proposed that HIIE increases glucose tolerance and insulin sensitivity (Cockcroft et al, 2015). This response to HIIE is due to a closed integration between the different body systems, especially the metabolic and immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…This method is considered a time-efficient way to improve health outcomes. Furthermore, Cockcroft et al (2015) showed that a single bout of HIIE (8 × 1-min at 90% of the peak power, interspersed by 1.25 min recovery at 20 W) is an effective alternative to moderate intensity exercise to improve glucose tolerance, insulin sensitivity, and fat oxidation immediately after exercise. Studies have shown that high intensity intermittent exercise (HIIE) alone or combined with strength exercise promoted changes in metabolic and inflammatory responses (Meckel et al, 2009, 2011; Zwetsloot et al, 2014; Cabral-Santos et al, 2015; Lira et al, 2015; Wadley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is most likely to participate in repetitive training sessions and competition events on a daily basis and for prolonged periods of time. Exercise training has been shown to promote a number of positive health- and performance-related adaptations in both adults and children [68,69,70]. It would be very interesting to know whether the pro-oxidant and, more importantly, the anti-oxidant mechanism respond to a training stimulus in the pediatric population.…”
Section: Responses To Chronic Exercisementioning
confidence: 99%
“…The risk of nocturnal hypoglycemia after HIIE in youth with T1D is poorly understood, but is likely due to HIIE having greater insulin sensitizing effects than MIE (Cockcroft et al. 2015). This is indirectly supported in the present study by an increase in the insulin:CHO ratio in both exercise conditions but not CON, with a larger increase after HIIE.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adolescents a single bout of time efficient high‐intensity interval exercise (HIIE) has been shown to improve glucose tolerance and insulin sensitivity (Cockcroft et al. 2015), suggesting that HIIE may be a strategy to manage glycemic control in youth with T1D. While an acute bout of HIIE has been shown to improve postprandial and 24‐h glycemic control in adults with type two diabetes mellitus (Gillen et al.…”
Section: Introductionmentioning
confidence: 99%